Factors affecting adoption of Smart watch and Fitness Band (Journal of Informatics Education and Research, 2025)
Awareness about health is a current development among the consumers, so is the tendency to make use of wearable healthcare devices. Smartwatch is the most popular wearable healthcare devices. Fitness bands also are popular for monitoring basic parameters of human body at consumer level. Most researches are done with the perspective of the technological or medical side pertaining to this topic. This technology is a part of non-conventional stream, that impact on the acceptance of the technology. Hence, the developers and manufacturers are eager to find out important factors that dominates the consumer’s behaviour.